Preparation method of gradient cobalt-free lithium-rich positive electrode material
By regulating the order of addition of precursor salt solution and rapid nucleation-assisted solvent thermal method, a full-concentration gradient cobalt-rich lithium-rich cathode material with high capacity and cyclic stability was prepared, solving the material stability and preparation complexity in the prior art. The problem of simplified process and excellent electrochemical properties are achieved.
Patent Information
- Application Number
- CN202411384226.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-24
AI Technical Summary
The existing cobalt-free lithium-rich cathode materials have problems in cycle stability and capacity attenuation. The preparation process is complex and the operating condition accuracy requirements are high, which limits its application.
By regulating the order of addition of precursor salt solutions, the Ni/Mn concentration gradient is achieved by regulating the order of addition of precursor salt solutions, thereby preparing a full-concentration gradient cobalt-rich lithium-rich cathode material with high capacity and cyclic stability.
It significantly improves the structure and electrochemical stability of the cathode material, simplifies the preparation process, is simple to operate, has good large-scale application prospects, and shows excellent electrochemical performance in lithium-ion batteries.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode material preparation, and in particular to an effective method for preparing a full concentration gradient cobalt-free lithium-rich positive electrode material by controlling the order of adding a precursor salt solution and combining a rapid nucleation-assisted solvothermal method. Background Art
[0002] With the rise of the electric vehicle market, lithium-rich layered oxide cathode materials (Li 1+ x TM 1-x O2, TM = Mn, Ni, Co, etc., 0< x ≤0.33) due to its high specific capacity (>250 mAh g -1 ) and mature preparation process. In recent years, with the serious shortage of transition metal resources, the development of cobalt-free lithium-rich layered cathode materials has become a top priority. However, at the same time, the problems of capacity decay and poor cycle stability faced by cobalt-free cathode materials have largely limited their practical application.
[0003] Based on the transition metal concentration gradient control strategy, lithium-rich cathode materials with lower voltage decay and higher performance can be cleverly designed. Conceptually, the gradient lithium-rich cathode from the highly active center to the solid surface should have higher cycling stability and be able to maintain high capacity and suppress voltage decay. In addition, compared with the heterogeneous core-shell structure, the gradient material can reduce structural dislocation and strain, making it more mechanically stable during electrochemical cycling. CN115663178A discloses a method for preparing a positive electrode material with a gradient structure of cobalt and vanadium elements. By setting a transition component between the active component and the protective component, the concentration of the active component gradually decreases from the inside to the outside of the positive electrode material, while the concentration of the protective component gradually increases, thereby improving the rate performance and cycle stability of the positive electrode material; CN115360332A discloses a method for preparing a gradient ternary coated graphene positive electrode material. After cobalt is coated on a nickel-manganese binary precursor, graphene is deposited on the surface to improve the rate performance and cycle performance of the material; CN112624207A discloses a lithium-rich manganese-based lithium positive electrode material with a full concentration gradient distribution. The preparation method comprises the following steps: slowly pumping a salt solution with a low manganese content into a salt solution with a high manganese content, and pumping the high manganese content solution into a reactor at a certain flow rate, regulating the feed rate and pH value under a nitrogen atmosphere, preparing a precursor by a coprecipitation reaction, and finally obtaining linearly changing Ni and Mn elements after sintering, thereby improving the energy density and cycle performance of the material.
[0004] According to the analysis of background technology, it is necessary to conduct innovative research in simplifying the preparation method and optimizing the element concentration gradient, so as to provide a unique strategy to better regulate the microstructure and further optimize the overall performance of the material, thereby promoting its commercial application. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art, such as shortage of element resources for the selection of positive electrode materials, complex gradient control process and high precision requirements for operating conditions, and to provide a simple, effective and excellent method for preparing a stable cobalt-free lithium-rich positive electrode material, that is, by regulating the order of adding precursor salt solutions and adopting a rapid nucleation-assisted solvothermal method, different Ni / Mn concentration gradients from the core to the surface interface are achieved, thereby obtaining a high-capacity core and a cycle-stable surface, thereby improving the structure and electrochemical stability of the positive electrode material.
[0006] To achieve the purpose of the invention, a method for preparing a gradient cobalt-free lithium-rich cathode material by regulating the order of adding a precursor salt solution and combining a rapid nucleation-assisted solvothermal method is provided according to the technical requirements of the present invention. The specific contents and technical solutions are as follows:
[0007] On the one hand, the present invention provides a method for preparing a full concentration gradient cobalt-free lithium-rich positive electrode material, which mainly comprises the following steps:
[0008] Step S1, the Mn source and the Ni source are manganese sulfate monohydrate and nickel sulfate hexahydrate respectively, three different stoichiometric ratios of Ni source and Mn source are weighed and dissolved in a mixed solution of deionized water and anhydrous ethanol, and the mixture is vigorously stirred and ultrasonicated until the solution is clear and transparent, and the solutions are marked as solution A, B, and C respectively;
[0009] Step S2, dissolving a certain stoichiometric ratio of ammonium carbonate precipitant in deionized water, marked as solution D;
[0010] Step S3, pouring the solution A obtained in S1 into the inner lining of the hydrothermal reactor, and then quickly pouring the precipitant solution D obtained in S2, stirring thoroughly, and then quickly adding solutions B and C in sequence and stirring;
[0011] Step S4, subjecting the mixed solution obtained in S3 to a hydrothermal reaction to prepare a gradient precursor;
[0012] Step S5, filtering and washing the precursor obtained in step S4 with deionized water;
[0013] Step S6, placing the precursor washed in step S5 in a vacuum drying oven for drying to obtain a precursor powder;
[0014] Step S7, mixing and grinding the dried precursor powder and lithium carbonate in a certain stoichiometric ratio in an agate mortar, placing the mixture in a muffle furnace and calcining it at a high temperature under an O2 atmosphere to obtain a cobalt-free lithium-rich positive electrode material with a full Ni / Mn concentration gradient;
[0015] Further, in step S1, three different stoichiometric ratios of Ni source and Mn source are respectively n Li2MnO3 m LiMn 0.5 Ni 0.5 O2 (n / m = 5 / 5, 3 / 7, 1 / 9) is calculated, A is 5 / 5, B is 3 / 7, and C is 1 / 9;
[0016] Further, in step S1, the volume ratio of deionized water to anhydrous ethanol is 2:1;
[0017] Furthermore, in step S2, to ensure complete precipitation of Ni and Mn, the amount of the precipitant ammonium carbonate is 1.5 times the sum of the amounts of the Ni source and Mn source materials of the above three different stoichiometric ratios;
[0018] Furthermore, in step S3, when adding the precipitant to the hydrothermal kettle, it is necessary to pour it in quickly and evenly to allow the bulk material to rapidly nucleate. When adding solutions B and C in sequence quickly, stirring is required;
[0019] Further, in step S4, the total amount of the mixed solution accounts for less than 70% of the capacity of the hydrothermal reactor, the temperature of the hydrothermal reaction is 200 °C, and the reaction time is controlled within 10-12 h;
[0020] Further, in step S6, the temperature of drying the precursor is 80°C;
[0021] Furthermore, in step S7, the high temperature calcination process includes pre-sintering and constant temperature sintering performed in sequence, and the heating rate is set to 5°C / min. The pre-sintering temperature is 550°C and the sintering time is 2-3 hours; the constant temperature sintering temperature is 800-900°C and the sintering time is 10-12 hours;
[0022] Further, in order to obtain cobalt-free lithium-rich cathode materials with different gradient conditions, the order of adding the precursor salt solution can be selected from A+B+C or C+B+A in the above step S3, and the corresponding cathode materials are marked as 5 / 5+3 / 7+1 / 9 or 1 / 9+3 / 7+5 / 5;
[0023] Furthermore, the gradient cobalt-free lithium-rich positive electrode materials prepared in the above steps all have a multi-ring structure of "layer-by-layer coating".
[0024] On the other hand, the present invention provides the preparation of homogeneous materials for comparison, that is, using the A, B or C solution in the above step S1 alone to react quickly with the precipitant D, and the subsequent steps are the same, and finally three types of cobalt-free lithium-rich positive electrodes of 5 / 5, 3 / 7, and 1 / 9 are obtained respectively.
[0025] The advantages of the present invention are embodied in the following aspects:
[0026] 1. The present invention can obtain a multi-ring gradient cathode material with "layer-by-layer coating" by adjusting the order of adding the precursor salt solution and using a rapid nucleation-assisted solvothermal method, which effectively solves the problem of poor consistency in the production and preparation of gradient materials. The gradient of the transition metal can be precisely adjusted to obtain a full concentration gradient cathode material with a high-capacity core and a cyclically stable surface. This design significantly inhibits the formation of the spinel phase in the cathode material after cycling, effectively reduces the occurrence of adverse phase changes, and ensures the integrity of the active particles after long-term cycling.
[0027] 2. Compared with other methods for stabilizing the crystal structure, the present invention does not require complicated preparation processes such as additional element doping or surface coating deposition. It is simple to operate, highly controllable, and has good prospects for large-scale application.
[0028] 3. The full concentration gradient cobalt-free lithium-rich cathode material prepared by the method of the present invention significantly improves the electrochemical performance after being assembled into a lithium-ion battery. In particular, in the absence of any structural modification and electrolyte optimization, the first cycle discharge capacity can reach 329.6 mAh g at 0.1 C. -1 , it still has excellent capacity retention after 200 cycles under 1C conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a cross-sectional SEM morphology of the homogeneous cobalt-free lithium-rich positive electrode material particles prepared in Comparative Example 1 before charge and discharge cycles.
[0031] Figure 2 This is a cross-sectional SEM morphology of the gradient cobalt-free lithium-rich positive electrode material particles prepared in Example 1 before charge and discharge cycles.
[0032] Figure 3 This is a macroscopic SEM morphology of the homogeneous cobalt-free lithium-rich positive electrode material prepared in Comparative Example 1 after charge and discharge cycles.
[0033] Figure 4 This is a macroscopic SEM morphology of the gradient cobalt-free lithium-rich positive electrode material prepared in Example 1 after charge and discharge cycles.
[0034] Figure 5It is a charge and discharge curve diagram of the first cycle of button-type half-cells of cobalt-free lithium-rich positive electrode materials prepared in Comparative Examples 1, 2, 3 and Examples 1 and 2 at 0.1 C.
[0035] Figure 6 This is a long-term cycle diagram of button-type half-cells made of cobalt-free lithium-rich positive electrode materials at 1 C, prepared in Comparative Examples 1, 2, 3 and Examples 1 and 2. DETAILED DESCRIPTION
[0037] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments in this application can be combined with each other.
[0038] The present invention provides a preparation method for obtaining a full concentration gradient cobalt-free lithium-rich positive electrode material by regulating the order of adding precursor salt solutions. The method mainly comprises: step S1, the Mn source and the Ni source are monohydrated manganese sulfate and hexahydrated nickel sulfate, respectively, three different stoichiometric ratios of Ni source and Mn source are weighed and dissolved in a mixed solution of deionized water and anhydrous ethanol, and vigorously stirred and ultrasonicated until the solution is clear and transparent, and marked as solutions A, B, and C respectively; step S2, a certain stoichiometric ratio of ammonium carbonate precipitant is dissolved in deionized water, marked as solution D; step S3, the solution A obtained in S1 is poured into the lining of the hydrothermal reactor, and then the precipitant solution D obtained in S2 is quickly poured in, and after sufficient stirring, the precipitant solution D is quickly added in sequence. Solution B and solution C are stirred; step S4, the mixed solution obtained in S3 is subjected to hydrothermal reaction to prepare a gradient precursor; step S5, the precursor obtained in step S4 is filtered and washed with deionized water; step S6, the precursor washed in step S5 is placed in a vacuum drying oven for drying to obtain a precursor powder; step S7, the dried precursor powder is mixed and ground evenly with lithium carbonate in a certain stoichiometric ratio in an agate mortar, and the mixture is placed in a muffle furnace and calcined at high temperature in an O2 atmosphere to obtain a cobalt-free lithium-rich positive electrode material with a full Ni / Mn concentration gradient.
[0039] In the method described in the present invention, the order of adding three precursor salt solutions with different stoichiometric ratios is controlled, and a gradient precursor is prepared by a rapid nucleation-assisted solvothermal method, and then mixed and ground with lithium carbonate of the corresponding stoichiometric ratio, and a high-performance gradient cobalt-free lithium-rich cathode material is obtained by high-temperature solid phase sintering. It is found that the order of adding the precursor salt solution corresponds to the chemical formula n Li2MnO3 m LiMn 0.5 Ni 0.5O2 (n / m = 5 / 5, 3 / 7, 1 / 9), when prepared in the order of 5 / 5+3 / 7+1 / 9, has an ion source-rich core layer, a transition layer, and a stable outer shell layer. The resulting positive electrode material has the best structural stability and the best comprehensive electrochemical performance.
[0040] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.
[0041] Example 1
[0042] First, 3 mmol of MnSO4∙H2O and NiSO4∙6H2O were mixed in a 0.5 Li2MnO3·0.5 LiMn 0.5 Ni 0.5 O2 was dissolved in 8.3 mL of deionized water at a stoichiometric ratio and stirred until completely dissolved. 4.2 mL of ethanol was added to the supernatant mixture and ultrasonicated to obtain solution A, which was poured into the reactor. Then 25 mL of 0.43 mol / L (NH4)2CO3 solution D was quickly added to the metal salt solution A. In the second step, 3 mmol of MnSO4∙H2O and NiSO4∙6H2O were added at a ratio of 0.3Li2MnO3·0.7 LiMn 0.5 Ni 0.5 O2 was dissolved in 8.3 mL of deionized water at a stoichiometric ratio and stirred until completely dissolved. 4.2 mL of ethanol was added to the supernatant mixture and ultrasonicated to obtain solution B. Finally, 3 mmol of MnSO4∙H2O and NiSO4∙6H2O were added at a ratio of 0.1 Li2MnO3·0.9 LiMn 0.5 Ni 0.5 The stoichiometric ratio of O2 was dissolved in 8.3 mL of deionized water and stirred until completely dissolved. 4.2 mL of ethanol was added to the above supernatant mixture and ultrasonically treated to obtain solution C. The prepared metal salt solutions were mixed and stirred in the order of solution A+D+B+C, and hydrothermally treated at 200°C for 10 hours to obtain a 5 / 5+3 / 7+1 / 9 precursor. The precursor mixture obtained by hydrothermal treatment was washed and filtered several times, and dried in a vacuum drying oven at 60-80°C. After adding stoichiometric lithium carbonate to the dried precursor powder and mixing and grinding for 1 h, it was transferred to a muffle furnace for high-temperature calcination. The calcination process included pre-sintering and constant temperature sintering in sequence. The heating rate was 5°C / min, wherein the pre-sintering temperature was 550°C and the sintering time was 3 h; the constant temperature sintering temperature was 850°C, the sintering time was 12 h, and the sintering atmosphere was an oxygen atmosphere. The particle cross-sectional morphology of the obtained gradient cathode material before cycling is shown in the following figure. Figure 2As shown in the figure, it has a remarkable "layer-by-layer" multi-ring structure, namely, an ion source-rich core layer, a transition layer, and a stable outer shell layer, which ensures structural stability while having excellent electrochemical performance. Figure 4 As shown in the figure, the spherical particles can still maintain a relatively complete morphology after 200 cycles of charge and discharge. The cathode material prepared above was assembled into a 2032 button half-cell for electrochemical performance characterization. Figure 5 , Figure 6 As shown, the first cycle discharge capacity is 329.6 mAh g -1 The capacity retention rate after 200 cycles at 1 C is 83.73%.
[0043] Example 2
[0044] The difference between this embodiment and embodiment 1 is that the order of adding the precursor salt solution is reversed, i.e., C+B+A, to obtain a 1 / 9+3 / 7+5 / 5 precursor, and the subsequent calcination process is the same as that of embodiment 1. The electrochemical performance of the positive electrode material assembled into a 2032 button half-cell prepared by the above method is shown in FIG. Figure 5 , Figure 6 As shown, the first cycle discharge capacity is 261.2 mAh g -1 The capacity retention rate after 200 cycles at 1 C is 88.28%.
[0045] Comparative Example 1
[0046] A total of 9 mmol of MnSO4∙H2O and NiSO4∙6H2O were prepared by mixing 0.5 Li2MnO3·0.5 LiMn 0.5 Ni 0.5 The stoichiometric ratio of O2 was dissolved in 25 mL of deionized water. After magnetic stirring until completely dissolved, 12.5 mL of ethanol was added to the supernatant mixture and ultrasonically treated for 10 minutes. 25 mL of 0.43 mol / L (NH4)2CO3 solution was quickly added to the metal salt solution and hydrothermally treated at 200°C for 10 hours to obtain a 5 / 5 precursor. The subsequent washing, drying and calcination processes were the same as in Example 1. The cross-sectional morphology of the particles of the obtained homogeneous positive electrode material before cycling is as follows Figure 1 As shown in the figure, due to the internal stress of the material during the sintering process, radial cracks appear in the particles. The primary particles are arranged tightly and unevenly, and no layered structure appears. The particle morphology after the cycle is as follows Figure 3 As shown in the figure, most of the spherical particles have been broken. The cathode materials prepared above were assembled into 2032 button-type half-cells for electrochemical performance characterization. Figure 5 , Figure 6 As shown, the first cycle discharge capacity is 258.3 mAh g -1, the capacity retention rate after 200 cycles under 1 C conditions is only 46.41%.
[0047] Comparative Example 2
[0048] The difference between this comparative example and comparative example 1 is that the stoichiometric ratio of the Ni source to the Mn source is different, that is, the total amount of 9 mmol of MnSO4∙H2O and NiSO4∙6H2O is 0.3 Li2MnO3·0.7 LiMn 0.5 Ni 0.5 The stoichiometric ratio of O2 was weighed, and the subsequent steps were the same as those in Comparative Example 1 to obtain a 3 / 7 homogeneous positive electrode. The electrochemical performance of the 2032 button half-cell assembled with the positive electrode material prepared by the above method is as follows: Figure 5 , Figure 6 As shown, the first cycle discharge capacity is 248.7 mAh g -1 The capacity retention rate after 200 cycles at 1 C is 81.41%.
[0049] Comparative Example 3
[0050] The difference between this comparative example and comparative example 1 is that the stoichiometric ratio of the Ni source to the Mn source is different, that is, the total amount of 9 mmol of MnSO4∙H2O and NiSO4∙6H2O is 0.1 Li2MnO3·0.9 LiMn 0.5 Ni 0.5 The stoichiometric ratio of O2 was weighed, and the subsequent steps were the same as those in Comparative Example 1 to obtain a 1 / 9 homogeneous positive electrode. The electrochemical performance of the positive electrode material prepared in the above method to assemble a 2032 button half-cell is shown in Figure 5 , Figure 6 As shown, the first cycle discharge capacity is 227.8 mAh g -1 The capacity retention rate after 200 cycles at 1 C is 89.93%.
[0051] The above is only a preferred embodiment of the present invention, but the present invention is not limited thereto. The technical combination extended and deformed on the technical concept of the present invention should also be regarded as the content disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a gradient cobalt-free lithium-rich positive electrode material, characterized in that: The preparation method comprises the following steps: Step S1, dissolving three Ni sources and Mn sources with different stoichiometric ratios in a mixed solution of deionized water and anhydrous ethanol, vigorously stirring and ultrasonicating until the solution is clear and transparent, and marking them as solutions A, B, and C respectively; Step S2, dissolving a certain stoichiometric ratio of ammonium carbonate precipitant in deionized water, marked as solution D; Step S3, pouring the solution A obtained in S1 into the inner lining of the hydrothermal reactor, and then quickly pouring the precipitant solution D obtained in S2, stirring thoroughly, and then quickly adding solutions B and C in sequence and stirring; Step S4, subjecting the mixed solution obtained in S3 to a hydrothermal reaction to prepare a gradient precursor; Step S5, filtering, washing and drying the obtained precursor to obtain precursor powder; Step S6, mixing and grinding the dried precursor powder and lithium carbonate in a certain stoichiometric ratio evenly, placing the mixture in a muffle furnace for high-temperature calcination to obtain a cobalt-free lithium-rich positive electrode material with a full Ni / Mn concentration gradient.
2. The preparation method according to claim 1, characterized in that In step S1, the volume ratio of the Ni source and the Mn source dissolved in the solvent of deionized water and anhydrous ethanol is 2:
1.
3. The preparation method according to claim 1, characterized in that In step S1, three different stoichiometric ratios of Ni source and Mn source are respectively n Li2MnO3 m LiMn 0.5 Ni 0.5 O2(n / m = 5 / 5, 3 / 7, 1 / 9) is calculated, where A is 5 / 5, B is 3 / 7, and C is 1 / 9.
4. The preparation method according to claim 1, characterized in that In step S2, to ensure complete precipitation of Ni and Mn, the amount of the precipitant ammonium carbonate is 1.5 times the sum of the amounts of the Ni source and Mn source materials of the above three different stoichiometric ratios.
5. The preparation method according to claim 1, characterized in that In step S3, when adding the precipitant to the hydrothermal kettle, it is necessary to pour it in quickly and evenly to allow the bulk material to rapidly nucleate. When adding solutions B and C in sequence quickly, stirring is required.
6. The preparation method according to claim 1, characterized in that In step S4, the temperature of the hydrothermal reaction is 180-220°C, preferably 200°C, and the reaction time is 8-12 h, preferably 10 h.
7. The preparation method according to claim 1, characterized in that In step S5, the temperature for drying the precursor is controlled at 70°C-90°C, preferably 80°C.
8. The preparation method according to claim 1, characterized in that In step S6, the amount of lithium carbonate added is 1.2 to 1.5 times the total molar amount of the precursor.
9. The preparation method according to claim 1, characterized in that In step S6, the high temperature calcination process includes pre-sintering and constant temperature sintering in sequence, with a heating rate of 5°C / min. The pre-sintering temperature is 550°C and the sintering time is 3 hours; the constant temperature sintering temperature is 850°C and the sintering time is 12 hours, and the sintering atmosphere is an oxygen atmosphere.
